(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the design thinking skills of students of the Department of Mathematics in the Colleges of Basic Education. In order to achieve the goal of the research, the following questions was put: 1) What is the level of design thinking skills among students of the mathematics department (fourth stage / morning) in the faculties of basic education? 2) What is the significance of the statistical difference at the significance level (0.05) between the average scores of students of faculties of basic education (fourth stage) departments of mathematics in the design thinking skills test according to the gender variable? The research sample consisted of (309) male and female students from the mathematics departments / fourth stage in the faculties of basic education, for the first semester of the academic year (2021-2022 AD). The design thinking skills test consisted of (10) essay problems (each problem included five sub-paragraphs of design thinking skills), and the results showed the following: 1) Weak level of design thinking skills among students of faculties of basic education in the departments of mathematics / fourth stage 2) There is a statistically significant difference in design thinking skills between males and females in the faculties of (Basic Education) Departments of Mathematics / Fourth Stage and in favor of females. In light of the results of this research, some recommendations that may contribute to improving the level of design thinking among students can be presented, which are: A) Reconsidering the formulation of curricula in faculties of education in line with the requirements to raise the level of design thinking skills among students of mathematics departments in a manner that takes into account individual differences in terms of the logical arrangement and sequence of information. b) Enriching the mathematical curriculum in colleges with various activities that motivate students to think in a design way. Also, some suggestions can be made A) Conducting studies similar to this research dealing with students of the four stages in the departments of mathematics in other universities. b) Examining the relationship between design thinking skills and achievement among university students in the faculties of basic education.